Effect Of Profitability, Leverage, Composition of the Board of Commissioners, Audit Committee and Fiscal Loss Compensation on Tax Avoidance in Banking Companies in BEI - Siregar, Pardomuan; Pakpahan, Ardy Johannes; Sipahutar, Tetty Tiurma Uli (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
This study aims to determine the relationship between profitability, leverage, and composition of the board of commissioners, audit committee, tax loss compensation on tax avoidance in companies banks listed on the Indonesia Stock Exchange in 2017 – 2019 The research method used is a quantitative research method with a descriptive approach. The research population is 39 companies. The sampling technique used is purposive sampling. Based on the results of the study showed that partially profitability has a positive effect on tax avoidance, but leverage, the composition of the board of commissioners, audit committee, and fiscal loss compensation on tax avoidance. The results of the study simultaneously show that the variables of profitability, leverage, composition of the board of commissioners, audit committee and compensation have no simultaneous effect on tax avoidance.